PRODUCTION NATURE AND CONSTRAINTS OF WOMEN LIVESTOCK FARMERS IN KANO STATE, NIGERIA - Ojo, O. A.; Issa, F.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the production nature and constraints of women livestock farmers in Kano State, Nigeria. Multi-stage sampling procedure was used to select 90 respondents for the study. The target population for the study comprised of women farmers in three local governments in Kano State namely; Kumbotso, Bunkure and Kura. Primary data were collected with the aid of structured questionnaire. Data collected were analyzed using frequency, percentages, pie-charts and bar-charts. The results obtained revealed that more than half (52.44%) of the respondents fell within the age bracket of (19-34) years. Many young and middle-aged women were involved in livestock production. About 50.0% were married, while 59.76% had a household size of (1-10), those with smaller households kept more livestock. From the results of the livestock raised, 37.80% of the women kept goats, 15.85% kept Cattle while 2.44% kept Camel. The results also revealed that the major constraint to production was the high cost of feed, which had the highest ranking. Women play a very important role in livestock production, their age, marital status and family size all influence the category of livestock reared and the herd size of livestock kept however, they encounter several challenges which limits livestock production. This study therefore recommends that women farmers should come together to form cooperatives so as to pool their resources to source for production inputs at affordable prices.